Opportunistic Termination - Alexander Stremitzer (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
If a seller delivers a good non-conforming to the contract, Article 2 of the UCC as well as European warranty law allows consumers to choose between some money transfer and termination. Termination rights are, however, widely criticized, mainly for fear that the buyer resorts to "opportunistic termination", i.e. takes non- conformity as a pretext to get rid of a contract he no longer wants. We show that the possibility of opportunistic termination might actually have positive ef- fects. Under some circumstances, it will lead to redistribution in favour of the buyer without any loss of efficiency. Moreover, by curbing the monopoly power of the seller, a regime involving termination increases welfare by enabling a more efficient output level in a setting with multiple buyers.
Keywords: L40; C7; K12; D30; 330; contract law; warranties; breach remedies; termination; harmonization; Vertragsrecht; Garantie; Lieferanten-Kunden-Beziehung; Opportunismus; Spieltheorie; Wohlfahrtseffekt; Theorie